المصالح المرسلة في المذهب المالكي - بن السايح، محمد (جامعة عمار ثليجي بالأغواط - كلية العلوم الإنسانية والاجتماعية - قسم العلوم الإسلامية, 2014)
Common among scholars is that Maalikis more schools taking interests sent, and they are responding so dump the provisions based on the asset, otherwise all sects take that asset, and Imam Malik Allah's mercy did not write the assets or notation, like him in this, such as Imam Abu Hanifa may Allah be pleased with him , and differs from the Imam Shafi'i after him where to put the rules of science assets in his famous letter (letter). Our scientists have stated that Maalikis elders are the ones who laid the rules of the assets of their beliefs through the fatwas of Imam Malik, where they have developed these assets from his fatwa God's mercy.
Keywords: المذاهب الفقهية; الفقه الإسلامي; الفقه المالكي; أصول الفقه; المصالح المرسلة; الأدلة الشرعية